Emplacing a Cooling-Limited Rhyolite Lava Flow: Similarities with Basaltic Lava Flows - Magnall, Nathan; James, Mike R.; Tuffen, Hugh; Vye-Brown, Charlotte (Frontiers in Earth Science, 2017)
Accurate forecasts of lava flow length rely on estimates of eruption and magma properties and, potentially more challengingly, an understanding of the relative influence of characteristics such as the apparent viscosity, the yield strength of the flow core, or the strength of the surface crust. Consequently, even the most straightforward models of lava advance involve sufficient parameters that constraints can be relatively easily fitted within the uncertainties involved, at the expense of gaining insight. Here, for the first time, we incorporate morphological observations from during and after flow field evolution to improve model constraints and reduce uncertainties. After demonstrating the approach on a basaltic lava flow (Mt. Etna, 2001), we apply it to the 2011-12 Cordón Caulle rhyolite flow, where unprecedented observations and syn-emplacement satellite imagery of an advancing silica-rich lava flow have indicated an important crustal influence on flow emplacement. Our results show that an initial phase of viscosity-controlled advance at Cordón Caulle was followed by later crustal control, accompanied by formation of flow surface folds and large-scale crustal fractures. Where the lava was unconstrained by topography, the cooled crust ultimately halted advance of the main flow and led to the formation of breakouts from the flow front and margins, influencing the footprint of the lava, its advance rate, and the duration of flow advance. Highly similar behaviour occurred in the 2001 Etna basaltic lava flow. The processes controlling the advance of crystal-poor rhyolite and basaltic lava flow therefore appear similar, indicating common controlling mechanisms that transcend profound rheological and compositional differences.